Peran dan Tanggung Jawab Notaris/PPAT dalam Penerapan Prinsip Mengenali Pengguna Jasa di Kota Gorontalo - Nurul Inayah Muchlisa Syarifudin; Nirwan Junus; Mohamad Taufiq Zulfikar Sarson (Pemuliaan Keadilan, 2024)
Ministerial Regulation Number 4 of 2017 concerning the Principle of Recognizing Service Users for Notaries was created to reduce even members of the crime of money laundering in Indonesia. This Ministerial Regulation is applied in the position of Notary in order to implement Government Regulation Number 61 of 2021 concerning the reporting party in the Prevention and Eradication of Money Laundering Crimes The increasing number of Money Laundering Crimes involving notary services in an effort to link the origin of assets derived from predicate crimes is the cause of the implementation of the Principle of Recognizing Service Users The type of research in this thesis uses normative legal research with a descriptive writing type The problem approach uses a qualitative approach. Data and Data sources use secondary data consisting of primary, secondary, tertiary legal materials. Data collection methods with literature studies, documentary studies and interviews with several parties, including the Ministry of Law and Human Rights and the Notary itself.